2004
DOI: 10.1111/j.0001-2815.2004.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the haplotypes of MICA and MICB microsatellite and HLA‐B locus in the Guangzhou Han population

Abstract: The purpose of this study was to investigate the genetic polymorphisms and haplotypes of microsatellite locus in exon 5 of the MICA gene and intron 1 of the MICB gene and human leukocyte antigen-B (HLA-B) gene based on 106 samples of the Guangzhou Han population through means of polymerase chain reaction and the fluorescent technique (6-FAM). The corresponding haplotype frequencies, linkage disequilibrium values and relative linkage disequilibrium values were estimated based on population data. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…HLA-B*13 is one of a common allelic group (phenotype frequency ranges from 10 to 30%) found in the Chinese population, and the distribution of HLA-B alleles in the controls of the present study was similar to that of the general population in southern China (Feng et al 2004; Liang et al 2005; Shi et al 2006; Yang et al 2006). In addition, the HLA-B*1301 allele, a member of the HLA- B*13 group in the southern Chinese population, is a specific allele in Asians, but is absent in whites and blacks (Cao et al 2001; Lin et al 1995; Williams et al 2001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…HLA-B*13 is one of a common allelic group (phenotype frequency ranges from 10 to 30%) found in the Chinese population, and the distribution of HLA-B alleles in the controls of the present study was similar to that of the general population in southern China (Feng et al 2004; Liang et al 2005; Shi et al 2006; Yang et al 2006). In addition, the HLA-B*1301 allele, a member of the HLA- B*13 group in the southern Chinese population, is a specific allele in Asians, but is absent in whites and blacks (Cao et al 2001; Lin et al 1995; Williams et al 2001).…”
Section: Discussionsupporting
confidence: 81%
“…The frequencies of HLA-B*1301 and HLA-B*1302 are variably distributed in different regions of China. The frequency of HLA-B*1301 in southern Chinese is higher than that in northern Chinese (Feng et al 2004; Middleton et al 2004; Shi et al 2006; Yang et al 2006). Rapid economic development, as occurring in China, could generate a highly mobile work force.…”
Section: Discussionmentioning
confidence: 79%
“…The strong association between STR_MICA and D6S2810 with the HLA‐B gene, described in previous population studies (Bolognesi et al. , 2001; Feng et al. , 2004; Grubic et al.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, the haplotypes STR_MICA*A4–HLA‐B*27 ; STR_MICA*A5–HLA‐B*35 ; STR_MICA*A5.1–HLA‐B*44, reported in these studies, were not observed or were not in significant LD in the present analysis. When our results were compared with those obtained from a Chinese population (Feng et al. , 2004; Tian et al.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, discrepancies were detected in the distribution of MICA-STR (Table 5) [25]. However, these discrepancies were most likely the result of different techniques used in each study.…”
Section: Discussionmentioning
confidence: 82%